2005
DOI: 10.1007/s00213-005-2236-0
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related vagotonic effect of zolpidem in rats

Abstract: Zolpidem not only caused a longer and deeper sleep but also led to an elevated cardiac vagal activity at a specific dose in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Zolpidem in contrast had no significant effect on blood pressure in humans (Cashman et al, 1987) or in rats (Mailliet et al, 2001). Others report conflicting changes in RR intervals, depending on the dose of zolpidem administered but mainly due to a change in cardiac vagal tone, rather than on sympathetic outflow (Chen et al, 2005). These data fit well with our report of the effects of different modulators on tonic GABA inhibition.…”
Section: Functional Significance Of Tonic Gabaergic Inhibitionsupporting
confidence: 91%
“…Zolpidem in contrast had no significant effect on blood pressure in humans (Cashman et al, 1987) or in rats (Mailliet et al, 2001). Others report conflicting changes in RR intervals, depending on the dose of zolpidem administered but mainly due to a change in cardiac vagal tone, rather than on sympathetic outflow (Chen et al, 2005). These data fit well with our report of the effects of different modulators on tonic GABA inhibition.…”
Section: Functional Significance Of Tonic Gabaergic Inhibitionsupporting
confidence: 91%
“…Our results from zolpidem administration in the CFS-exposed rats are consistent with the data of previous studies that have tested zolpidem effects in the normal rat. For example, some studies have shown that the intraperitoneal administration of zolpidem at 3 or 10 mg/kg doses increases SWS in normal rats [10, 26, 54]. Another study in the normal adult rat reported that the latency to SWS was reduced after administration of zolpidem at doses of 2.5, 5, and 7.5 mg/kg [29].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies in both humans [24, 28, 40, 4749, 62, 63, 82] and animals [10, 34, 35, 54, 64, 95, 110, 111] have tested the hypnotic effects of eszopiclone and zolpidem. These studies have suggested that both eszopiclone and zolpidem are nearly equally effective hypnotics with very few or no adverse side effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, several prior studies have demonstrated that the measurement of HRV while a person is awake may not reflect their HRV state during sleep (13,14), since some delicate alternations -such as sympathetic activation accompanied by hypertension -are not readily detected without conducting a sleep study (13,15). Recent improvements in sleep research techniques (13,(15)(16)(17)(18) now allow us to test whether sleep patterns and sleep-related cardiac autonomic regulation are influenced by long-term night shift work in nurses. It therefore seems appropriate to undertake an exploration of the changes in HRV which accompany sleep, in order to clarify the pathways between cardiovascular disease and nurses engaged in shift working.…”
mentioning
confidence: 99%